Effects of parent-child aggression, maternal warmth and child processing mechanisms on hostile attribution bias - Zdravkovic, Ana (2012)
The present study aimed to expand the current conceptualization of hostile attribution bias (HAB) development by examining the effects of maternal parent-child aggression (PCA) and warmth on HAB development. In addition, child attentional control and latent mental structures were included as mechanisms through which experiences impact HAB, because Social Information-Processing theory and the intentionality development literature support this relation. Four hundred and twenty seven children were assessed at 2, 5.5, 7.5- and 10.5-years on measures of PCA, maternal warmth, child latent mental structures, child attentional control, and hostile attribution bias. Structural equation modeling supported the specified indicators for the latent factors of PCA, warmth, and attentional control. Additionally, the hypothesis that PCA is related to more hostile attributions and warmth is related to less hostile attributions, was supported in an initial model. The final model included the child mechanisms and indicated that warmth continued to be directly related to decreases in HAB, while PCA was indirectly related to increases in HAB through its relation to attentional control. This study contributes to the literature by expanding the types of hostile parenting that are related to HAB, including both warmth and PCA to predict HAB, and accounting for child mechanisms when measuring parent effects on HAB. Implications for further examination of the development of HAB include examining the contribution of maternal HAB and child emotions, as well as determining the applicability of this research to preventative interventions